Libraries of Islam: Religious Traditions of Spreading Science - Surtikanti, R (KnE Social Sciences, 2018)
This article is the result of historical research that discusses the development of libraries in Muslim societies during the period of Islamic Caliphate in the Middle East region and beyond. The results showed that different types of libraries were developed from one period to another within different Islamic caliphates. The development of this library is supported by the principle of seeking and dissemination of knowledge that was practiced directly by the Muslim community at that time. In addition, it is also influenced by other economic, social and cultural conditions that developed during this period. Keywords: libraries history, Islamic libraries, Islam